Sistem Monitoring Pengatur Suhu dan Kelembaban pada Kandang Jangkrik berbasis Internet of Things (Studi Kasus Budidaya Jangkrik Perorangan di Kabupaten Blitar) - Andy Wiranto; Heru Nurwarsito (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Unstable temperature and humidity are problems that are often faced by cricket farmers. However, cricket breeders still use manual methods to identify the environmental conditions of the cage. This requires a monitoring system that is able to regulate the temperature and humidity in the cricket cage, thus facilitating the process of monitoring and controlling the climate. The system is built using Internet of Things (IoT) technology. In the application of IoT, a communication protocol between entities is needed to exchange data. MQTT is a messaging communication protocol that requires low resources. Climate control uses a microcontroller that implements a detection algorithm on a system that is made capable of recognizing the environmental conditions of the cage using the MQTT protocol. Accuracy Data collection using sensors is 1.03% for the relative error of temperature measurement data and 0.47% for the relative error of humidity measurement data. The MQTT protocol has a performance with an average delay parameter value of 345 ms, and a packet loss of 0%.